Exploring new routes in genetic studies on human aging and longevity - Montesanto,Alberto; Passarino,Giuseppe; De Benedictis,Giovanna (My University, 2007)
The past few decades has witnessed a growing scientific interest in genetic studies on human aging and longevity. This growing interest may be explained by the increasing number of elderly subjects in developed countries over the last 50 years due to the continued improvements in health care. Such a fast increase of these population segments represent a huge problem for the societies in terms of social care and welfare. The difficulty in understanding the biological basis of human aging and longevity is mainly represented by (i) the cohort and the population-specificity of human aging and longevity, (ii) the lack of a clear and objective definition of the phenotype, (iii) the polygenic nature of the human longevity. On the basis of these observations, the studies reported here represent new approaches for the study of human aging and longevity. They were carried out on data obtained from the Calabrian population, characterized by high genetic homogeneity and a scarce level of immigration due to geographical, historical and social reasons. The first approach we used was to analyze the spatial distribution of long-lived individuals in Calabria. Using this approach, we verified that the spatial distribution of such individuals in this region is not uniform. In addition, by using surname data, we verified a significant correlation between population inbreeding and male longevity in a particular area of this region. The second approach is based on the application of a Cluster Analysis with well established geriatric parameters to identify aging phenotypes in the Calabrian population. The results obtained show that, the aging phenotypes recognized by Cluster Analysis are consistent from a geriatric point of view and have a clear genetic component.Finally, using a multilocus approach, we analyzed the influence of genetic variability of candidate genes on survival at old age in good health. On the basis of a synthetic survival curve built using historic mortality data from the Italian population and using multiple regression models, we found that genetic factors influence survival at advanced ages in good health in a sex and age specific way. The results reported here show that the application of these new approaches may be useful in human aging and longevity studies. Furthermore, they demonstrate that a multidisciplinary approach is necessary to analyze human aging and longevity.
Dottorato di Ricerca in Molecular Bio-Pathology, XIX Ciclo, a.a.2006-2007
Keywords: Genetica; Invecchiamento; Longevità